2022
DOI: 10.3390/biom12101419
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Biomarkers and Unique Pathways in Different Phenotypes of Heart Failure with Preserved Ejection Fraction

Abstract: Heart failure with preserved ejection fraction (HFpEF) accounts for around 50% of all heart failure cases. It is a heterogeneous condition with poorly understood pathogenesis. Here, we aimed to identify unique pathogenic mechanisms in acute and chronic HFpEF and hypertrophic cardiomyopathy (HCM). We performed unbiased, comprehensive proteomic analyses of plasma samples from gender- and BMI-matched patients with acute HFpEF (n = 8), chronic HFpEF (n = 9) and HCM (n = 14) using liquid chromatography–mass spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Several bioinformatic analyses have shown that LRG1 may serve as a useful biomarker in cardiovascular diseases ( 20 23 ). For instance, one study demonstrated that LRG1 is elevated in patients with acute coronary syndrome compared with healthy controls ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several bioinformatic analyses have shown that LRG1 may serve as a useful biomarker in cardiovascular diseases ( 20 23 ). For instance, one study demonstrated that LRG1 is elevated in patients with acute coronary syndrome compared with healthy controls ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several bioinformatic analyses have shown that LRG1 may serve as a useful biomarker in cardiovascular diseases (20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…However, its diagnostic or pathogenic role has not previously been demonstrated in HF. In light of these important functions associated with FKBPL, it is likely that it may have a role in the development of HF-particularly HFpEF-since inflammation and microvascular dysfunction are hallmark features of HFpEF [14]. Thus, this study evaluated the role of FKBPL in the development of cardiac hypertrophy and HFpEF using in vitro models of cardiomyoblasts exposed to a hypertensive stimulus, angiotensin-II (Ang-II), and/or the FKBPL mimetic AD-01, as well as human plasma samples from people with different forms of HFpEF and controls.…”
Section: Introductionmentioning
confidence: 99%